Impact of COVID-19 in Immunosuppressed Children With Neuroimmunologic Disorders. Issue 1 (10th January 2022) - Olivé-Cirera, Gemma; Fonseca, Elianet; Cantarín-Extremera, Verónica; Vázquez-López, María; Jiménez-Legido, María; González-Álvarez, Verónica; Ribeiro-Constante, Juliana; Camacho-Salas, Ana; Martí, Itxaso; Cancho-Candela, Ramon; Martínez-González, María Jesús; Saiz, Albert; et al.
Abstract : Background and Objectives: To investigate whether children receiving immunosuppressive therapies for neuroimmunologic disorders had (1) increased susceptibility to SARS-CoV2 infection or to develop more severe forms of COVID-19; (2) increased relapses or autoimmune complications if infected; and (3) changes in health care delivery during the pandemic. Methods: Patients with and without immunosuppressive treatment were recruited to participate in a retrospective survey evaluating the period from March 14, 2020, to March 30, 2021. Demographics, clinical features, type of immunosuppressive treatment, suspected or confirmed COVID-19 in the patients or cohabitants, and changes in care delivery were recorded. Results: One hundred fifty-three children were included: 84 (55%) female, median age 13 years (interquartile range [8–16] years), 79 (52%) on immunosuppressive treatment. COVID-19 was suspected or confirmed in 17 (11%) (all mild), with a frequency similar in patients with and without immunosuppressive treatment (11/79 [14%] vs 6/74 [8%], p = 0.3085). The frequency of neurologic relapses was similar in patients with (18%) and without (21%) COVID-19. Factors associated with COVID-19 included having cohabitants with COVID-19 ( p < 0.001) and lower blood levels of vitamin D ( p = 0.039). Return to face-to-face schooling or mask type did not influence the risk of infection, although 43(28%) children had contact with a classmate with COVID-19. Clinic visits changed from face to face to remote for 120 (79%) patients; 110 (92%) were satisfied with the change. Discussion: In this cohort of children with neuroimmunologic disorders, the frequency of COVID-19 was low and not affected by immunosuppressive therapies. The main risk factors for developing COVID-19 were having cohabitants with COVID-19 and low vitamin D levels.